Propofol as a substitute for amobarbital in Wada testing. Issue 11 (November 2015) - Chiu, Albert Ho Yuen; Bynevelt, Michael; Lawn, Nicholas; Lee, Gabriel; Singh, Tejinder Pal
Highlights With functional MRI (fMRI) and awake craniotomy techniques, the Wada test has fallen into disuse. This has lead to relative unavailability of amobarbital, the agent of choice. The Wada test is useful in patients with equivocal fMRI results. Propofol is the next best studied agent for use in Wada testing after amobarbital. Awareness of the utility of the Wada as a preoperative test is important.